Kinetics and Mechanism of Oxidation of Hexamethylenediaminetetraacetatocobaltate(II) Complex by Periodate Ion in Aqueous Medium. Issue Volume 7:Issue S1(2010) (2010) - Naik, R. M.; Rai, B. Kumar J.; Rastogi, R.; Yadav, S. B. S.
Abstract : The kinetics and mechanism of oxidation of [Co II HDTA] 4- (Where HDTA=Hexamethylenediamine tetraacetic acid} by periodate ion has been studied in aqueous acidic medium. The reactions has been investigated spectrophotometrically at λmax = 580 nm under pseudo- first -order condition by taking large excess of oxidant [IO4 ] at pH = 4.0±0.02, I = 0.1 M (CH3 COONa + NaNO3 ).and temperature = 30± 0.1 ° C The electron transfer reaction between [Co II HDTA] 4- and [IO4 - ] obeys inner sphere reaction pathway through the formation of long-lived intermediate complex which finally get converted into a corresponding [Co III HDTA] 3- complex as final reaction product. The experimental observations have shown that the reaction obey first- order dependence in [Co II HDTA] 4- -. The variation of pseudo-first-order rate constants (kobs ) with[IO4 - ], keeping other reaction variables fixed at constant value was found to obey the rate law: kobs =a[IO4 - ]2/b+c[IO4 - ], which is consistent with a three step mechanistic scheme. The values of kobs are almost constant with increasing pH, which can be attributed to the reaction of deprotonated form of [Co III HDTA] 4- complex only, in the entire pH region. Eyring's equation has been used to calculate the thermal or activation parameters and found to be, ΔH # = 28.69 kJ mole –1 ; ΔS # = – 481.13 J K -1 mole –1 respectively and support the proposed mechanistic scheme.